Sentiment view lexicon (EN) - Wiegand, Michael; Ruppenhofer, Josef; Schulder, Marc (Universität, 2019)
This gold standard contains sentiment expressions (verbs, nouns and adjectives) that have been annotated according to their (prior) sentiment view....
Kind of data: Textual data in tab-separated format
Deposit date: 2019-07-31
Gesehen am 16.10.2019
Keywords: Forschungsdaten; Datenbank